PEMBUATAN PETA PENUTUPAN LAHAN MENGGUNAKAN FOTO UDARA YANG DIBUAT DENGAN PARAMOTOR DI TAMAN NASIONAL LORE LINDU (TNLL) (STUDI KASUS DESA PAKULI KECAMATAN GUMBASA KABUPATEN SIGI) - Amelia, Nur Rizky; Akhbar, Akhbar; Arianingsih, Ida (Jurnal Warta Rimba, 2015)
The research was conducted on Lore Lindu National Park (LLNP) around Pakuli Village, Gumbasa, District of Sigi from February to April 2014. The objectives of the study is to establish land cover maps through aerial photograph interpretation as the basis for the park management in the future. The methods used were correction, mosaic and interpretation from the aerial photographs taken. To validate the results, site observation was conducted followed by the analysis of land cover maps and their existing sizes. Based on the established maps recorded through paramotor, the size of land cover of the Pakuli Village 2014 ha can be described as 98.95 rice field (28.28%), 83.54 ha secondary forest (23.80%), 77.44 ha primary forest (22.13%), 13 coconut plantation (3.72%), 4.79 ha bush (1.37%), 14.73 ha rivers (4.21%), 33.74 ha open land (9.64%). Keywords: land cover, aerial photographs, Lore Lindu National Park, paramotor